Evaluation of Urban Spaces from the Perspective of Universal Design Principles: The Case of Konya/Turkey - Alkan Meshur, H. Filiz (TeMA - Journal of Land Use, Mobility and Environment, 2016)
During the process of accessing services provided within urban interior and outer spaces the elderly and disabled individuals encounter with a myriad of problems due to the limitations posed by structured environments. This limitation hinders elderly and disabled individuals from mobility without assistance, which in turn negatively affects their full participation to urban and social life. Rearrangement of urban spaces to meet the needs of elderly and disabled individuals would correspondingly bolster life quality of the entire range of users. Within the scope of present research, as mandated by universal design principles to stick to plans and designs approaches inclusive for all users, it is aimed to conduct evaluations on the use of urban outer spaces situated within Konya city center. In the hypothetical and theoretical part of this paper, the perception of disability throughout historical process has been examined from a sociological perspective. In addition, concept of universal design, its principles and gravity have also been elaborated. In the part dealing with the case study, outer spaces within Konya city center have been analyzed with respect to universal design principles and a range of suggestions have been developed.